Design of Imidazo[1,2-a]pyridine-Based Donor–Acceptor Chromophores through a Multicomponent Approach - Stahlberger, Mareen; Mergel, Milada; dos Santos, John Marques; Matulaitis, Tomas; Nieger, Martin; Zysman-Colman, Eli; Bräse, Stefan (Synlett, 2024)
A series of donor-acceptor chromophores was synthesized bearing a 3-aminoimidazo[1,2-a]pyridine donor motive. Through DFT calculations, different combinations of the ImPy donor motive and different electron acceptors were assessed. In combination with an anthraquinone acceptor, the calculated ΔEST values were in range to suggest that these compounds would emit via thermally activated delayed fluorescence. Based on these findings, a series of ImPy-Aq emitters with different geometries and substitution patterns was synthesized through GBB-3CR and Suzuki coupling reactions. According to preliminary experimental data, the compounds were only slightly emissive at ambient temperatures due to a combination of low radiative rates and competing non-radiative deactivation pathways.
Keywords: multicomponent reaction; imidazo[1,2-a]pyridine; Suzuki coupling; thermally activated delayed fluorescence; donor-acceptor chromophores